2015
DOI: 10.1152/ajprenal.00467.2014
|View full text |Cite
|
Sign up to set email alerts
|

Renal human organic anion transporter 3 increases the susceptibility of lymphoma cells to bendamustine uptake

Abstract: Chronic lymphatic leukemia (CLL) is often associated with nephritic syndrome. Effective treatment of CLL by chlorambucil and bendamustine leads to the restoration of renal function. In this contribution, we sought to elucidate the impact of organic anion transporters (OATs) on the uptake of bendamustine and chlorambucil as a probable reason for the superior efficacy of bendamustine over chlorambucil in the treatment of CLL. We examined the effects of structural analogs of p-aminohippurate (PAH), melphalan, chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Drug-induced cis-stimulation of the reference substrate uptake was observed previously for various influx as well as for efflux transporters and numerous compounds. Hagos et al demonstrated 24% to 86% stimulation of OAT3 (SLC22A8) as well as OAT4 (SLC22A11)-mediated estrone sulfate uptake by melphalan, respectively [ 45 ]. Irinotecan caused 93% stimulation of estrone sulfate uptake by OATP1B1 (SLCO1B1), as reported by Marada et al (2015) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced cis-stimulation of the reference substrate uptake was observed previously for various influx as well as for efflux transporters and numerous compounds. Hagos et al demonstrated 24% to 86% stimulation of OAT3 (SLC22A8) as well as OAT4 (SLC22A11)-mediated estrone sulfate uptake by melphalan, respectively [ 45 ]. Irinotecan caused 93% stimulation of estrone sulfate uptake by OATP1B1 (SLCO1B1), as reported by Marada et al (2015) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bendamustine engages cell death through both apoptotic and non-apoptotic pathways, thereby retaining activity even in cells with dysfunctional apoptotic machinery [ 24 ]. Recently, it has been reported that some membrane transporters might also contribute to the cytotoxic effect of bendamustine [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of co-culture with CAFs, the induction of resistance to gemcitabine, cytarabine, and bendamustine was observed, though resistance to bendamustine was not induced in the presence of exosomes from CAFs. Considering that the uptake of bendamustine into lymphoma cells is thought to be through human organic cation transporter 1 (OCT1) and human organic anion transporter 3 (OAT3) [ 29 , 30 ], the difference in drug transporters between anti-pyrimidine drugs and bendamustine might have caused this discrepancy. In addition, our finding that resistance to bendamustine was not observed in the presence of exosomes suggests that drug resistance by CAFs is induced by varying mechanisms.…”
Section: Discussionmentioning
confidence: 99%